Welbeck Park: the impact of landscape management on parkland animals 1769 TO 1879 - Bestwick, Susan (2019)
Eighteenth and nineteenth century landscape parks have been the focus of scholarly attention by historians and geographers from differing perspectives. parkland studies have included landscape and garden design, political and economic aspects, farming and forestry. This thesis takes a different approach as the key aim of the study is to discover the impact of landscape management within Welbeck Park, Nottinghamshire, on parkland animals. The thesis examines the tenures of the 3rd to the 5th Dukes of Portland, 1769-1879 by means of a case study approach. This will enable the close study of parkland animals and the implications of landscape change at Welbeck from an environmental perspective.